2009
DOI: 10.1007/s00359-009-0441-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a perception of prosodic cues in bat communication: contact call classification by Megaderma lyra

Abstract: The perception of prosodic cues in human speech may be rooted in mechanisms common to mammals. The present study explores to what extent bats use rhythm and frequency, typically carrying prosodic information in human speech, for the classification of communication call series. Using a two-alternative, forced choice procedure, we trained Megaderma lyra to discriminate between synthetic contact call series differing in frequency, rhythm on level of calls and rhythm on level of call series, and measured the class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…syllable repetition rate and number of syllables per call). Such acoustic parameter changes are widespread across mammals, suggesting common coding rules that function to influence the behavior of conspecifics: bats [9], [25], [29], [58], primates [24], [59], [60], tree shrews [27], ground squirrels [61], [62], dogs [28], [63], African elephants [64], and guinea pigs [65]. Moreover, particular sound qualities such as rapid signal onset, short duration click-like energy pulses, upward FM sweeps, rapid amplitude modulations, and noisy frequency spectra routinely alter the attention, arousal, and affect of listeners [66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…syllable repetition rate and number of syllables per call). Such acoustic parameter changes are widespread across mammals, suggesting common coding rules that function to influence the behavior of conspecifics: bats [9], [25], [29], [58], primates [24], [59], [60], tree shrews [27], ground squirrels [61], [62], dogs [28], [63], African elephants [64], and guinea pigs [65]. Moreover, particular sound qualities such as rapid signal onset, short duration click-like energy pulses, upward FM sweeps, rapid amplitude modulations, and noisy frequency spectra routinely alter the attention, arousal, and affect of listeners [66].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of graded acoustic parameter changes are widespread across mammals, suggesting a common coding rule in mammalian communication sounds [23], [24], [25], [26], [27], [28]. In bats, there is recent evidence that greater false vampire bats ( Megaderma lyra ) make systematic changes to the call structure, such as the number and repetition rate of syllables, according to the intensity level of agonistic interactions [9], and such changes provide prosodic cues that listeners may evaluate [29]. Nonetheless, important questions still surround the accuracy with which the acoustic signals reflect the internal affective state of the caller and what influence these sounds have on a listener.…”
Section: Introductionmentioning
confidence: 99%
“…SOCIAL COMMUNICATION BY SOUND depends on acoustic signals composed of basic spectro-temporal elements-syllables-that are combined in temporal patterns. Both the types of vocal syllables emitted and the temporal emission patterns, or sequencing, carry significant information related to the behavioral state of the sender and can influence the behavior of conspecifics: bats (Bastian and Schmidt 2008;Gadziola et al 2012a;Gould and Weinstein 1971;Janssen and Schmidt 2009;Russ et al 2005), primates (Fichtel and Hammerschmidt 2002;Fischer et al 2002;Rendall 2003), tree shrews (Schehka et al 2007), ground squirrels (Leger and Owings 1977;Mateo 2010), dogs (Pongracz et al 2006;Yin and McCowan 2004), African elephants (Soltis et al 2009), and guinea pigs (Arvola 1974). An accurate interpretation of these social signals thus depends on appropriate analysis of the "acoustic context," defined here as the sequencing and temporal emission pattern of vocalizations within which they are presented.…”
mentioning
confidence: 99%
“…macrodactylus females returning to the colony; furthermore, the diversity of calls was affected by syllable type and unique syllable types led to specific calls. New evidence has suggested that Megaderma lyra can regularly modify the structure of their calls, including the number and repetition of syllables, according to competing strength ( Bastian & Schmidt, 2008 ), and signalers may convey their own properties in acoustic signals ( Janßen and Schmidt, 2009 ).…”
Section: Discussionmentioning
confidence: 99%